A novel strategy as a potential rapid therapy modality in the treatment of corneal ulcers: Fluconazole/vancomycin dual drug-loaded nanofibrous patches - CESUR, SÜMEYYE; BİNGÖL ÖZAKPINAR, ÖZLEM; TINAZ, GÜLGÜN; OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN (My University, 2023)
Corneal ulcer, which is brought on by a breach in the epithelial barrier, is a dangerous infection of the avascular corneal stroma. New treatment strategies are needed, suppressing the aggressive nature of the disease and including a combination of different drugs. In this study, vancomycin (VAN) and fluconazole (FLU) dual-drug loaded dual-layered polyvinyl alcohol and gelatin (PVA/GEL) nanofibrous patches are produced by electrospinning. Scanning electron microscopy (SEM) images show smooth surfaces are obtained for both pure and drug-loaded nanofibrous patches. The tensile test results report that loading the FLU and VAN separately into the PVA/GEL patches decrease both the tensile strength and elongation at break and it is further reduced when combining two drug-loaded layers in one patch. According to drug release results, the FLU and VAN-loaded nanofibrous patches show a controlled release profile extending up to 96 h. Moreover, PVA/GEL/FLU, PVA/GEL/VAN, and PVA/GEL/FLU/VAN nanofibrous patches display significant antimicrobial activity against Candida albicans and Staphylococcus aureus. SEM, 4\"-6diamidynofenyloindol (DAPI) staining, and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay show that PVA/FLU and PVA/GEL/FLU/VAN nanofibrous patches have a superior effect on NIH3T3 cell spreading and proliferation. The novelty of this study lays in the development of a potential dual drug rapid treatment for corneal ulcers of aggressive nature.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, KİMYASAL; POLİMER BİLİMİ; KİMYA, ORGANİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; ENGINEERING, CHEMICAL; POLYMER SCIENCE; CHEMISTRY, ORGANIC; MATERIALS SCIENCE, MULTIDISCIPLINARY; Genel Kimya Mühendisliği; Fizik Bilimleri; Organik Kimya; Polimerler ve Plastikler; Malzeme Kimyası; General Chemical Engineering; Physical Sciences; Organic Chemistry; Polymers and Plastics; Materials Chemistry; corneal tissue engineering; corneal ulcers; electrospinning; fluconazole; vancomycin